Integrating bioinformatics to explore HPV-31 and HPV-52 E6/E7 proteins: from structural analysis to antigenic epitope prediction - Cai, Qixue; Feng, Yifan; Dong, Wenbo; Meng, Yanling (Frontiers in Immunology, 2025)
IntroductionCervical cancer is the most common malignant neoplasm of the female reproductive tract. Infection with human papillomavirus (HPV) has been strongly associated with cervical cancer. Previous bioinformatics studies have examined the E6 and E7 proteins of high-risk HPV types; however, subtype-specific analyses for HPV-31 and HPV-52 remain limited. Understanding the structure and properties of the E6 and E7 proteins of HPV-31 and HPV-52 is crucial to elucidating their functions and advancing vaccine development.MethodsA bioinformatics approach was employed to predict the physicochemical properties, hydrophilicity, protein structure, glycosylation sites, phosphorylation sites, terminal positions, signal peptide cleavage sites, transmembrane regions, homology, and dominant epitopes of the E6 and E7 proteins of HPV-31 and HPV-52.ResultsFor HPV-31 E6, an instability index (II) of 43.93 indicated that the protein is unstable; potential B-cell epitopes were identified at residues 55–61 (RDDTPYG), 112–116 (PEEKQ), and 125–131 (FHNIGGR), while T-cell epitopes were predicted at residues 45–53 (FAFTDLTIV) and 72–80 (KVSEFRWYR). HPV-52 E6 exhibited an instability index (II) of 55.57, with B-cell epitopes at residues 110–119 (LCPEEKERHV) and 129–141 (MGRWTGRCSECWR), and T-cell epitopes at residues 45–53 (FLFTDLRIV) and 82–87 (SLYGKT). HPV-31 E7, with an instability index (II) of 51.05, exhibited B-cell epitopes at residues 8–17 (QDYYLDLQP), 16–20 (QPEAT), 29–41 (PDSSDEEDVIDEP), and 42–48 (AGQAKPDT), and T-cell epitopes at residues 7–15 (TLQDYVLDL) and 82–90 (LLMGSFGIV). HPV-52 E7, with an instability index (II) of 49.15, exhibited B-cell epitopes at residues 11–19 (YILDLQPET), 23–27 (HCYEQ), 29–38 (GDSSDEEDTD), and 36–48 (DTDGVDRPDGQAE), and T-cell epitopes at residues 53–59 (NYYIVTY) and 84–90 (MLLGTLQ).DiscussionIn summary, the E6 and E7 proteins of HPV-31 and HPV-52 contain dominant epitopes for both T cells and B cells. These findings delineate subtype-specific immunogenic regions and establish a foundation for experimental validation and vaccine design.